2022
DOI: 10.1021/acsabm.2c00373
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer-Functionalized Nanodiamonds as Safe and Efficient Drug Carriers for Cancer Therapy: Nucleus Penetrating Nanoparticles

Abstract: Nanodiamonds (NDs) are increasingly being assessed as potential candidates for drug delivery in cancer cells and they hold great promise in overcoming the side effects of traditional chemotherapeutics. In the current work, carboxylic acid functionalized nanodiamonds (ND-COOH) were covalently modified with poly­(amidoamine) dendrimer (PAMAM) to form amine-terminated nanodiamonds (NP). Unlike ND-COOH, the chemically modified nanodiamond platform NP revealed a pH-independent aqueous dispersion stability, enhancin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…[477] Many investigators have tested the conjugation of NDs to several types of drug molecules, including epirubicin, [478] DOX, [479][480][481][482] tamoxifen, [483] cetuximab, [484] and amonafide, [485] and assessed their delivery capabilities, uptake, and internalization after reaching a tumor region. Patil et al [486] demonstrated that NDs could be covalently conjugated to poly(amidoamine) dendrimer (PA-MAM) via an ultrasound probe sonication to form ND-PAMAM nanoconjugates. The capabilities of cabazitaxel (CTX) as a guest molecule to be localized within the accessible nanoconfined spaces of ND-PAMAM conjugates and internal cavities of the PA-MAM dendrimers were investigated.…”
Section: Drug-delivery and Targeted Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…[477] Many investigators have tested the conjugation of NDs to several types of drug molecules, including epirubicin, [478] DOX, [479][480][481][482] tamoxifen, [483] cetuximab, [484] and amonafide, [485] and assessed their delivery capabilities, uptake, and internalization after reaching a tumor region. Patil et al [486] demonstrated that NDs could be covalently conjugated to poly(amidoamine) dendrimer (PA-MAM) via an ultrasound probe sonication to form ND-PAMAM nanoconjugates. The capabilities of cabazitaxel (CTX) as a guest molecule to be localized within the accessible nanoconfined spaces of ND-PAMAM conjugates and internal cavities of the PA-MAM dendrimers were investigated.…”
Section: Drug-delivery and Targeted Cancer Therapymentioning
confidence: 99%
“…Patil et al. [ 486 ] demonstrated that NDs could be covalently conjugated to poly(amidoamine) dendrimer (PAMAM) via an ultrasound probe sonication to form ND‐PAMAM nanoconjugates. The capabilities of cabazitaxel (CTX) as a guest molecule to be localized within the accessible nanoconfined spaces of ND‐PAMAM conjugates and internal cavities of the PAMAM dendrimers were investigated.…”
Section: Emerging Applications Of Fluorescent Nanocarbons In Biomedicinementioning
confidence: 99%
“…4,5 Thus, the carrier needs to be appropriately designed in terms of size/surface chemistry for endosomal escape and for efficient nucleus delivery. 1−3 Some of the examples of nucleus delivery include a tiopronincoated Au nanoparticle of 2 nm size for gene delivery to the nucleus, 6 peptide-conjugated chitosan nanoparticle (25 nm, 100 nm) for protein delivery to the nucleus, 7 3−4 nm carbon dot for nuclear delivery of the molecular drug, 8 dendrimerfunctionalized nanodiamond of 200−400 nm size for nuclear delivery of the molecular drug, 9 cell-penetrating protein-based protein delivery to the nucleus via endosomal escape, 10 and polythymidine-based oligonucleotide delivery to the nucleus via mechanotransduction. 11,12 Recent studies show that nonendocytic and direct cell membrane penetration-based cell delivery can be a powerful alternative for subcellular delivery, as these processes can bypass the endosomal/lysosomal entrapment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Delivery of small-molecule drugs, genes, macromolecules, and proteins into the cell and subcellular compartment is important for efficient therapeutic performance. , In particular, efficient cell nucleus delivery of exogenous materials can greatly improve the biochemical activity. In a common approach, synthetic carriers are used for nucleus delivery where drug-loaded/conjugated carriers enter into the cell via cellular endocytosis. However, such a delivery approach restricts the nuclear delivery of exogenous materials as they enter the cytosol with a vesicular coating (not freely available in the cytosol) and trapped in the endosome/lysosome (and often enzymatically degraded). , Thus, the carrier needs to be appropriately designed in terms of size/surface chemistry for endosomal escape and for efficient nucleus delivery. Some of the examples of nucleus delivery include a tiopronin-coated Au nanoparticle of 2 nm size for gene delivery to the nucleus, peptide-conjugated chitosan nanoparticle (25 nm, 100 nm) for protein delivery to the nucleus, 3–4 nm carbon dot for nuclear delivery of the molecular drug, dendrimer-functionalized nanodiamond of 200–400 nm size for nuclear delivery of the molecular drug, cell-penetrating protein-based protein delivery to the nucleus via endosomal escape, and polythymidine-based oligonucleotide delivery to the nucleus via mechanotransduction. , …”
Section: Introductionmentioning
confidence: 99%
“…Dendritic macromolecules have lots of unique properties, which are well-defined nanostructures and unique morphologies, high concentration of functional groups at the surface, high solubility in aqueous media, high monodispersity, low viscosity, and modification ability with functional molecules. These characteristics resulted in the development of dendritic nanostructures for a wide range of applications, including drug-delivery or gen-delivery systems, chemosensors, bioimaging, and tissue engineering. Induction of stimuli-responsivity to dendrimers by their modification with intelligent molecules has been known as an attractive field of study. The pH- or temperature-responsive dendrimers are among the highly important smart nanocarriers in drug- or gen-delivery technology, and the light-responsive dendrimers are highly applicable in bioimaging and photosensing applications. , Different types of dendrimers were modified with stimuli-responsive molecules using their surface functional groups, or in a classic approach, using a functional intelligent molecule as a core to growth of dendritic structures on the surface. Therefore, the presence of acid, amine, or hydroxyl functional groups on dendrimers is inevitable for their reaction with functional molecules.…”
Section: Introductionmentioning
confidence: 99%